Mindfulness and fear of hypoglycaemia in parents of children with Type 1 diabetes: results from Diabetes MILES Youth – The Netherlands. Issue 5 (27th February 2018) - Aalders, J.; Hartman, E.; Nefs, G.; Nieuwesteeg, A.; Hendrieckx, C.; Aanstoot, H.‐J.; Winterdijk, P.; van Mil, E.; Speight, J.; Pouwer, F.
Abstract: Aims: To identify the sociodemographic and clinical correlates of fear of hypoglycaemia among parents of children (aged 4–18 years) with Type 1 diabetes and to examine the relationships between parental fear of hypoglycaemia, mindfulness and mindful parenting. Methods: Sociodemographic, self‐reported clinical and psychological data were extracted from the cross‐sectional Diabetes MILES Youth – The Netherlands dataset. Questionnaires included the Hypoglycaemia Fear Survey – Parent Worry (parental fear of hypoglycaemia), the Freiburg Mindfulness Inventory – Short version (mindfulness) and the Interpersonal Mindfulness in Parenting Scale (mindful parenting). Results: A total of 421 parents (359 mothers) participated. Hierarchical linear regression analyses showed that greater parental fear of hypoglycaemia was related to younger parental age, low educational level, non‐Dutch nationality, more frequent blood glucose monitoring, and less general mindfulness. Adding mindful parenting to the model negated the previous contribution of general mindfulness. In this model, lower mindful parenting was related to greater parental fear of hypoglycaemia. In particular, parents with an increased ability to be less judgemental of themselves as parents and less reactive to emotions within parenting interactions reported less fear of hypoglycaemia. In total, 21% of the variance in parental fear of hypoglycaemia was explained. Conclusion: Parental fear of hypoglycaemia was associated largely with parental characteristics, including non‐modifiable sociodemographics (i.e. age, education, nationality) and modifiable psychological factors (i.e. mindful parenting). These findings suggest that it is important to further explore mindfulness‐based interventions for parents to reduce fear of hypoglycaemia next to interventions to reduce hypoglycaemia. What's new?: This is the first study to simultaneously examine both child and parent characteristics, in terms of sociodemographic, clinical and modifiable psychological factors (general mindfulness and mindful parenting), in relation to parental fear of hypoglycaemia. Greater parental fear of hypoglycaemia was related to younger parental age, low educational level, non‐Dutch nationality, more frequent blood glucose monitoring and less parental mindfulness. These findings can be used to identify parents who are at risk of fear of hypoglycaemia and to inform the development of mindfulness interventions targeted at reducing parental fear of hypoglycaemia.